Knowledge and practice on endotracheal tube suctioning among nurses in critical care wards at Hospital Universti Sains Malaysia - Nordin, Nur Najiha (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2021)
Endotracheal tube suctioning is a vital procedure in the critical care unit. It is a procedure that either can give benefits or harm to the patient. This research study is done to determine the level of knowledge and practice in endotracheal tube suctioning among nurses at the critical care wards at Hospital Universiti Sains Malaysia (HUSM). A crosssectional study was involving 113 respondents via random sampling. A questionnaire survey used for data collection from October 2020 to July 2021. The test used in this study was descriptive statistics and Pearson’s Chi-Square test using Statistical Package of Social Sciences (SPSS) version 26.0. The findings revealed that 61.3% of the nurses scored good knowledge while 37.7% scored poor knowledge. Meanwhile, for the practice, 92.1% of the nurses scored good practice while 7.1% scored poor practice. In addition, there was no significant association between the sociodemographic data (age, gender, level of education, working experience in critical care wards and working wards) with the nurses’ level of knowledge and practice on endotracheal tube suctioning (pvalue >0.05). Plus, there was no significant correlation between the level of knowledge and level of practice on endotracheal tube suctioning among nurses in critical care wards. As conclusion, majority of the nurses in critical care wards have good knowledge and practice on endotracheal tube suctioning.